2005
DOI: 10.1177/08830738050200081001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Brain Glucose Metabolism Positron Emission Tomography (PET) and Electroencephalography (EEG) in Children With Continuous Spike-and-Wave Activity During Slow-Wave Sleep

Abstract: We studied the relationship between brain glucose metabolism patterns and objectively measured interictal epileptiform abnormalities in six children with intractable epilepsy and continuous spike-and-wave activity during slow-wave sleep. Five of the six patients showed lateralized positron emission tomographic (PET) findings, with the hemisphere showing a relative increase in glucose metabolism concordant with the presumed origin of the generalized interictal spike activity delineated by quantitative electroen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
0
24
1
Order By: Relevance
“…35 Most quantitative studies of FDG-PET in CSWS have focused on cortical metabolism in CSWS. 31,36 Our group has previously demonstrated regional changes in cerebral metabolism in patients with CSWS using FDG-PET. 36 Focal hypermetabolism has been proposed as a hallmark of acute CSWS, with evolution to cortical hypometabolism in the residual stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Most quantitative studies of FDG-PET in CSWS have focused on cortical metabolism in CSWS. 31,36 Our group has previously demonstrated regional changes in cerebral metabolism in patients with CSWS using FDG-PET. 36 Focal hypermetabolism has been proposed as a hallmark of acute CSWS, with evolution to cortical hypometabolism in the residual stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…31,36 Our group has previously demonstrated regional changes in cerebral metabolism in patients with CSWS using FDG-PET. 36 Focal hypermetabolism has been proposed as a hallmark of acute CSWS, with evolution to cortical hypometabolism in the residual stage of the disease. 37,38 In the present study, only 9 of 16 patients in the acute phase of CSWS demonstrated cortical hypermetabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, PET studies using simultaneous scalp EEG recording reported that very frequent interictal epileptiform discharges, if present, were associated with glucose hyper metabolism in the presumed epileptogenic hemisphere. Cortical resection involving such glucose hypermetabolism was reported to result in a good seizure outcome [10, 39]. A plausible explanation for hypermetabolism on interictal PET is that very frequent interictal spike discharges may transiently increase glucose metabolic demands regionally (e.g.…”
Section: Role Of Scalp Video-eeg Monitoringmentioning
confidence: 99%
“…Previous studies also demonstrated that the frequency and spatial field of interictal spike activity were greater during sleep with spindles compared to wakefulness in children with various forms of epilepsies including focal epilepsy, Landau-Kleffner syndrome and continuous spike-waves during slow wave sleep (Nobili et al, 1999;2001;Luat et al, 2005). Previous studies describing the cyclic alternating pattern of sleep indicated that the phase A with K-complex and slow-waves may be an excitatory phase associated with increased frequency of interictal epileptiform discharges while phase B with low-voltage fast waves, including sleep spindles alone, may be an inhibitory phase (Terzano et al, 1991;Terzano et al, 1992;Zucconi et al, 2000;Eisensehr et al, 2001).…”
Section: Sleep May Alter the Overall Frequency But Not The Spatial DImentioning
confidence: 99%